Exploring the acceptance of 360° videos in virtual reality settings for teaching and learning - Evi Indriasari Mansor,; Marzni Mohamed Mokhtar,; Nurfadhlina Mohd Sharef, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Virtual Reality (VR) is a technology that has been widely adopted in supporting learning and educational purposes over recent years. It has shown enormous potential to pioneer education in the future, mainly through its immersive learning environments provided in 360° settings. We explore the possibility of using VR technology in supporting teaching and learning experience in class. This paper reports the perception of trainee teachers towards the acceptance of the use of 360° videos in VR settings for teaching and learning. Forty trainee teachers were grouped to create learning content using available 360° videos and rendering and processing them into a VR format. They viewed and experienced the content they developed using the ClassVR headset. The findings showed positive feedback on the use of 360° videos in facilitating immersive learning experiences.